2019
DOI: 10.1108/jpbm-07-2019-2464
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to the special issue on the past, present and future research on deliberate lookalikes

Abstract: Purpose The purpose of this paper is to present the contemporary thinking on deliberate lookalikes and to provide a better understanding of its key forms (counterfeits, copycats and no-name imitations) and markets (deceptive and non-deceptive). Design/methodology/approach This editorial contains a review of current and past literature on deliberate lookalikes along with summaries of all the articles accepted for publication in the special issue on deliberate lookalikes. The guest editors used academic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, various psychological and social factors related to the influence of counterfeit decision choices have been previously studied, however, the research showed mixed findings (Davcik et al , 2019; Prendergast et al , 2002). Some studies point out that although perceived risk significantly reduces (Riquelme et al , 2012) and value consciousness significantly increases (Hidayat and Diwasasri, 2013; Ang et al , 2001), attitudes towards counterfeiting, others find them to have no impacts (Bhatia, 2018; Phau and Teah, 2009).…”
Section: Contextual Background and Research Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, various psychological and social factors related to the influence of counterfeit decision choices have been previously studied, however, the research showed mixed findings (Davcik et al , 2019; Prendergast et al , 2002). Some studies point out that although perceived risk significantly reduces (Riquelme et al , 2012) and value consciousness significantly increases (Hidayat and Diwasasri, 2013; Ang et al , 2001), attitudes towards counterfeiting, others find them to have no impacts (Bhatia, 2018; Phau and Teah, 2009).…”
Section: Contextual Background and Research Objectivementioning
confidence: 99%
“…Additionally, social influence is found to significantly impact attitudes towards counterfeiting/piracy in some studies negatively (Ang et al , 2001) and in other studies positively (Moon et al , 2018; Riquelme et al , 2012). Likewise, some studies report a significant negative influence of ethical judgement on attitudes towards counterfeiting (Jiang et al , 2019; Quoquab et al , 2017) and purchase intention (Ha and Lennon, 2006) but others do not (Davcik et al , 2019). Given that the majority of these factors have not previously been studied within the Egyptian context, there is a need to investigate them so that global foreign brand producers/retailers can gain a better understanding of the Egyptian consumers' attitudes towards counterfeiting and their purchase intention and, hence, adopt the appropriate marketing strategies.…”
Section: Contextual Background and Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that "lookalike products" primarily consist of two types: counterfeit and copycat (Davcik et al, 2019;Jiang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Counterfeits are defined as products that are identical to a trademark registered to another party and that infringe the rights of the holder (Bian et al 2016). With an annual import value of more than $400 billion, they constitute about 7% of the world trade, and present a significant macromarketing concern (Davcik et al 2019; OECD/EUIPO 2016). Counterfeits are known to cause dissatisfaction among the patrons of the original, and a loss of sales for the genuine brand (Evans, Starr, and Brodie 2019).…”
Section: Introductionmentioning
confidence: 99%